Hydroxypropyl-β-Cyclodextrin-Complexed Resveratrol Enhanced Antitumor Activity in a Cervical Cancer Model: In Vivo Analysis - Hao, Xincai; Sun, Xiaodong; Zhu, Haizhen; Xie, Lixia; Wang, Xuanbin; Jiang, Nan; Fu, Pan; Sang, Ming (Frontiers in Pharmacology, 2021)
Trans-resveratrol (RES) exhibits a wide range of biological activities. Various methodological approaches have been established to improve the pharmacokinetic properties of RES. Moreover, additional in vivo studies are required to support clinical application. In this study, RES/HP-β-CD (RHSD) inclusion complex was prepared and characterized by FTIR, PXRD, DSC and NMR data. The eﬀect and potential mechanism of RHSD against cervical cancer were investigated in a mouse xenograft tumor model by qPCR assay, Western blot assay, and immunoﬂuorescence assay. Results showed that RHSD significantly decreased tumor growth compared with free RES, while the effect of preventing tumor growth was more prominent in vivo. Notably, RHSD could inhibit tumor development by suppressing the expression of HPV E6 and E7 oncogenes and upregulating P53 and Rb1 protein in cervical cancer. These findings demonstrated that RHSD was safe and potential for development of a new oral administration drug to treat cervical cancer.